Acute hemorrhagic cholecystitis with gallbladder rupture and massive intra-abdominal hemorrhage - Zachary Pickell; Krishnan Raghavendran; Maria Westerhoff; Aaron M. Williams (University of São Paulo, 2021)
Acute hemorrhagic cholecystitis is a rare, life-threatening condition that can be further complicated by perforation of the gallbladder. We describe a patient with clinical and radiologic findings of acute cholecystitis with a gallbladder rupture and massive intra-abdominal bleeding. Our patient is a 67-year-old male who presented with an ischemic stroke and was treated with early tissue plasminogen activator. His hospital course was complicated by a fall requiring posterior spinal fusion surgery. He recovered well, but several days later developed subxiphoid and right upper quadrant pain and an episode of hemobilia and melena. A computed tomography scan revealed an inflamed, distended gallbladder with indistinct margins and a large hematoma in the gallbladder fossa extending to the right paracolic gutter. The patient also developed hemodynamic instability concerning for hemorrhagic shock. He underwent an emergent laparoscopic converted to open subtotal fenestrating cholecystectomy with abdominal washout for management of his acute hemorrhagic cholecystitis with massive intra-abdominal hemorrhage. Prompt recognition of this lethal condition in high-risk patients is crucial for optimizing patient care.